The mediating effect of perceived value on customer loyalty of BMT NU East Java - Mohamad Mondir; Siti Habibatur Rahma (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – The purpose of this research is to analyze and examine the effect of Islamic marketing mix, service quality, and product quality on BMT customer loyalty, with perceived value as a mediating variable. Methodology – This study is a quantitative research with 200 samples of BMT NU East Java customers. It uses non-probability sampling, and data collected will be analyzed with the help of SPSS software to obtain statistical correlation and regression techniques (validity test, reliability test, classic assumption test, path analysis, t-test, and trimming test). Findings – The results show that service quality and product quality have a significant effect on perceived value and customer loyalty, while the Islamic marketing mix has no significant effect on perceived value and customer loyalty. Meanwhile, perceived value has a significant effect on customer loyalty. Perceived value can mediate the Islamic Marketing mix, service quality, and product quality variables in customer loyalty. Implications – This research provides input for related parties, especially BMT NU East Java and every further Islamic financial institution, to optimize services and financial products to get more attention from customers, both new customers and old customers. Originality – There is no research that discusses microfinance (BMT NU) using perceived value, product quality, service quality, and Islamic marketing mix as variables. These variables are variable that have most effect on loyalty of microfinance’s consumers.